2014
DOI: 10.1039/c4dt01098a
|View full text |Cite
|
Sign up to set email alerts
|

An insight into fluorescent transition metal complexes

Abstract: The emission from transition metal complexes is usually produced from triplet excited states. Owing to strong spin-orbit coupling (SOC), the fast conversion of singlet to triplet excited states via intersystem crossing (ISC) is facilitated. Hence, in transition metal complexes, emission from singlet excited states is not favoured. Nevertheless, a number of examples of transition metal complexes that fluoresce with high intensity have been found and some of them were even comprehensively studied. In general, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 55 publications
4
57
0
3
Order By: Relevance
“…Calculated copper C Q values reported here were adjusted to incorporate the more recent value of −19.8 fm 2 for Q( 63 Cu). 10 4 ] + ) = 1193.7 and 1099.5 ppm, respectively, for calculations with the 6-31+G* and 6-311+G* basis sets). The structure for [Cu(NCCH 3 ) 4 ] + is based on that determined by X-ray crystallography by Zhu and co-workers, 61 although in our case average bond length values were used, and tetrahedral symmetry about the copper atom was assumed.…”
Section: Articlementioning
confidence: 99%
“…Calculated copper C Q values reported here were adjusted to incorporate the more recent value of −19.8 fm 2 for Q( 63 Cu). 10 4 ] + ) = 1193.7 and 1099.5 ppm, respectively, for calculations with the 6-31+G* and 6-311+G* basis sets). The structure for [Cu(NCCH 3 ) 4 ] + is based on that determined by X-ray crystallography by Zhu and co-workers, 61 although in our case average bond length values were used, and tetrahedral symmetry about the copper atom was assumed.…”
Section: Articlementioning
confidence: 99%
“…However, in complexes containing an independent chromophoric centre based on an extended aromatic system, emission from the initial singlet excited state may compete with ISC, which results in the generation of either dual singlet/triplet emission [5,[15][16][17][18] or only singlet emission from an organic chromophore. [19][20][21][22][23] These unusual types of photophysical be-served emission is ligand-centred fluorescence that is atypical for complexes of this type, which usually display phosphorescence determined by strong spin-orbit coupling with the heavy-metal ion. DFT calculations of the electronic structure of the complexes showed that the contribution of the gold orbitals to the states responsible for emission is nearly negligible and results in a low intersystem crossing rate and suppression of phosphorescence in the complexes studied.…”
Section: Introductionmentioning
confidence: 99%
“…2 The presence of late transition metals exhibiting large spin--orbit coupling (SOC) in organic chromophores allows for facile tuning of the excited states, mainly because the SOC promotes very high rate (10 --12 s --1 ) intersystem crossing (ISC) from singlet into triplet excited states (quenching the fluorescence), and can facilitate the triplet → singlet radiative transition (phosphorescence), modifying the photochemistry and photophysics and, as a result, their potential applications. For this reason the fluorescence of transition metal compounds is very difficult to observe but not impossible, 3 and using perylene as chromophore, we have reported Pt II complexes of perylene and perylene monoimide with Pt σ--bonded directly to the perylene core, where the coordination of Pt has only a moderate quenching effect and the complexes show intense fluorescent emissions. We have reported also high fluorescence properties perylene derivatives with gold, palladium or platinum complex fragments attached to perylene through a tetrafluorophenyl linker, associated to the fact that the π--systems of the perylene and tetrafluorophenyl fragments are uncoupled; 4 or with an isocyanide group acts as a connector between a Au, Pd, Cr, Mo, W complex fragments and the perylene chromophore, for which theoretical calculations indicate a very weak interactions of the metal with the π--system of the perylene.…”
Section: Introductionmentioning
confidence: 99%